La tercería excluyente de dominio dentro del juicio ejecutivo, sus efectos, consecuencias y reforma a la normativa legal. - Cofre Trelles, Cristhian Jefferson (2013)
In this research, I have supported my hypothesis that the Exclusionary third party domain when it is introduced in the Executive Judgment, is to delay, delay your procedure is execution, by this entails several consequences such as no application of the Constitutional Principles.